MODEL INTERVENSI PEKERJA SOSIAL DALAM MENDUKUNG PEMBERDAYAAN DISABILITAS DI SENTRA WIRAJAYA KOTA MAKASSAR - FADILLAH, FRISKA; SAID, IRWANTI; HAERUDDIN (Jurnal Washiyah, 2026)
This study examines the social worker intervention model in the empowerment of persons with disabilities at Sentra Wirajaya, Makassar City. The research problem is divided into three main focuses: (1) the stages of intervention implemented by social workers in the empowerment process; (2) the supporting and inhibiting factors in the implementation of the intervention; and (3) the impact of the intervention on improving the independence and social functioning of the beneficiaries. This study employed a qualitative method with a descriptive approach. Research informants included social workers, the head of the center, and beneficiaries with disabilities. Data were gathered from primary and secondary sources through observation, in-depth interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing to obtain a comprehensive overview of the intervention process. The results indicate that the social worker intervention model is structured systematically through the stages of assessment, planning, implementation, and evaluation. Interventions are carried out at the micro, mezzo, and macro levels through individual accompaniment, group activities, vocational skills training, as well as advocacy and social network strengthening. The model has proven effective in enhancing the capabilities, self-confidence, economic independence, and social functioning of persons with disabilities, despite facing constraints such as limited resources and social stigma. The implications of this study are expected to serve as a reference for social service institutions in developing more effective and sustainable empowerment-based intervention models. Furthermore, enhancing social worker capacity, providing adequate rehabilitation facilities, and strengthening collaboration with various stakeholders are essential to creating an inclusive, disability-friendly environment that enables persons with disabilities to live independently and participate actively in society.